1989
DOI: 10.1111/j.1151-2916.1989.tb06231.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Bi‐Sr‐Cu‐O Subsolidus Diagram at 800°C with and without Lithium Carbonate

Abstract: Solid-phase relationships have been determined for the Bi203-Sr0-Cu0 system at 800°C in air with and without Li2C03 mineralizer. Two ternary compounds were detected with Bi : S r :Cu ratios of approximately 2 : 2 : I and a solid-solution phase I 1 -x:9+x:5 with 0 1~1 0 . 4 . The solid-solution phase is a 9 K superconductor at x =0.4. Two additional compounds with Bi:Sr:Cu ratios of approximately 4:9:1 and 2:7:2 are apparently stabilized by the presence of Li2C0,, but do not form without it. X-ray crystallograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…Attempts to grow crystals with higher Sr contents resulted in the formation of the true 2:2:1 phase, a related layered structure with a somewhat smaller stacking repeat distance. This phase is semiconducting and has been investigated previously [3,4,7].…”
Section: Effects Of Variable Strontium Contentmentioning
confidence: 98%
See 1 more Smart Citation
“…Attempts to grow crystals with higher Sr contents resulted in the formation of the true 2:2:1 phase, a related layered structure with a somewhat smaller stacking repeat distance. This phase is semiconducting and has been investigated previously [3,4,7].…”
Section: Effects Of Variable Strontium Contentmentioning
confidence: 98%
“…The ideal stochiometry, Bi 2 Sr 2 CuO 6 , is based on crystal structure analysis [2]. Previous work on ceramics with the 2201 structure [3,4] , demonstrated that the "ideal" 2201 phase is deficient in Sr and is actually a solid solution tolerating a range of Sr deficiency (x= 0.1-0.5). We also showed that with decreasing Sr content the ceramics exhibited a metal to semiconducting transition at nominal values of x between 0.25 and 0.5 [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is now recognized from a number of studies, that compounds having compositions corresponding to the general formula Bi 2 Sr 2 Ca n _ 1 Cu M O 4 + 2M , do not actually exist, but rather the compounds are formed with an apparent cation deficiency (e.g., Chippindale et al, 1988;Saggio et al, 1989;Ikeda et al, 1989). The one-layer compound is Sr-deficient compared to the ideal stoichiometry and can also contain Ca substitutions.…”
Section: Bismuth Strontium Calcium Cuprate (Bi 2 Sr 2 Ca^1cu Lt O 4 +mentioning
confidence: 99%
“…Indeed, these nominal compositions do not form singlephase material (Golden etal., 1991a, b). Studies of both the Bi-Sr-Cu-O and Bi-Sr-Ca-Cu-O systems indicate that a solid-solution range exists for the one-and two-layer superconducting phases (Saggio et al, 1989;Ikeda et al, 1989;Golden et al, 1991 a, b). There is some discrepancy as to the actual extent of the solid solution and also the temperatures of the phase formation, but this can probably be attributed to the use of both powders and bulk samples and the consequent difficulty in attaining phase equilibrium.…”
Section: Bi-sr-ca-cu-o Phase Equilibriamentioning
confidence: 99%
“…The quaternary phase relationships of the 2212 phase at 800°C have been investigated by Hong and Mason 8 and Saggio et al, 15 at 820°C by Muller and co-workers, 11,12 and at 850°C by Majewski and co-workers. 7, 16 Other equilibrium studies include those by MacManus-Driscoll and co-workers [17][18][19] and Schulze et al 20 For purposes of discussion, it is useful to designate the complicated BSCCO formulas with simplified abbreviations, as indicated in Table I.…”
Section: Introductionmentioning
confidence: 99%